Pengaruh Motivasi, Stres Kerja, Kompensasi Dan Lingkungan Kerja Terhadap Produktivitas Kerja Pada Karyawan Multimart Simbarwaringin - Ristanti, Ersa Mei; Febriyanto, Febriyanto (Jurnal Manajemen DIVERSIFIKASI, 2022)
The purpose of this study was to determine the effect of motivation, work stress, compensation and work environment on employee productivity at Multimart Simbarwaringin, Trimurjo district, Central Lampung district. The analytical method used is quantitative research. The object of this research is employees who work at Multimart Simbarwaringin, Trimurjo district, Central Lampung district. The total population is 40 respondents. Data collection techniques using literature study, interviews, observations, documentation and questionnaires. Data analysis techniques using SPSS 20 include testing instrument requirements, testing requirements analysis and testing hypotheses. Simultaneously the four variables show a positive and significant effect on employee work productivity, so in this case discussing motivation, work stress, compensation and the work environment related very important in a company or organization.Keywords: Motivation, work stress, compensation, work environment and employee productivity. Kata Kunci : Motivasi, Stres kerja, Kompensasi, Lingkungan Kerja dan Produktivitas Kerja Karyawan.